(untitled) (Journal of Advanced Veterinary and Animal Research, 2020)
Objectives: This study aimed to examine the effects of wet-to-dry bandages for the treatment of surgical wounds in goats. Materials and Methods: Three types of bandages, i.e., the calcium alginate gel, the homogenous platelet-rich plasma (PRP) gel dressing, and saline dressing, were used to promote the healing process for the management of wounds. Artificial circular wounds were created and treated with bandages to evaluate their effects on the wound healing process in 12 goats. The morphological parameters, i.e., diameters (cm), duration of healing, and wound contraction (cm), were evaluated to differentiate the postoperative sequelae on wound healing process up to day 30 in three different treatment groups of goats. Tissue specimens from the wounds were examined histopathologically on 1st, 3rd, 7th, and 30th postoperative days. Finally, the obtained data were analyzed using the Statistical Package for the Social Sciences 19 software. Results: The current study revealed that the contraction diameter was higher in calcium alginate gel and PRP gel treated group when compared to the saline dressing group. Aggregation of immunoreactive cells (neutrophils, macrophages, and lymphocytes), collagen fiber bundles among the cells, and proliferation of blood vessels were observed in the epidermis of calcium alginate gel, PRP gel treated and saline dressing wounds, which promote the healing process of wounds. In visual inspection, the number of reactive cells and proliferation of blood vessels were higher in the calcium alginate gel and PRP gel treated group than the saline dressing. Conclusion: In terms of epithelialization, epidermal characteristics, neovascularization, and infiltration of immunoreactive cells, the calcium alginate gel and the homogenous PRP gel dressings showed the best healing performance. Therefore, the present study suggests that clinicians could consider the calcium alginate gel dressing and homogenous PRP gel dressing as beneficial for wound care. J. Adv. Vet. Anim. Res., 7(4): 647-654, Dec 2020 http://doi.org/10.5455/javar.2020.g463